KEEFEKTIFAN MODEL STUDENT TEAMS ACHIVEMENT DIVISION BERBANTU MEDIA ULAR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI BINTORO 01 DEMAK (Universitas Negeri Semarang, 2018)
Abstract This research is motivated poor learning outcomes Elementary School fourth grade students Bintoro 01 Demak in social studies material natural resources and economic activities. The research was conducted in the fourth grade totaling 30 students by using technique that